Genetic variations in 3'UTRs of SMUG1 and NEIL2 genes modulate breast cancer risk, survival and therapy response - Cumova, Andrea; Vymetalkova, Veronika; Opattova, Alena; Bouskova, Veronika; Pardini, Barbara; Kopeckova, Katerina; Kozevnikovova, Renata; Lickova, Katerina; Ambrus, Miloslav; Vodickova, Ludmila; Naccarati, Alessio; Soucek, Pavel; et al. (Mutagenesis, 2021)
Breast cancer (BC) is the most frequent malignancy in women accounting for approximately 2 million new cases worldwide annually. Several genetic, epigenetic and environmental factors are known to be involved in BC development and progression, including alterations in post-transcriptional gene regulation mediated by microRNAs (miRNAs). Single nucleotide polymorphisms (SNPs) located in miRNA binding sites (miRSNPs) in 3'-untranslated regions of target genes may affect miRNA-binding affinity and consequently modulate gene expression. We have previously reported a significant association of miRSNPs in the SMUG1 and NEIL2 genes with overall survival in colorectal cancer patients. SMUG1 and NEIL2 are DNA glycosylases involved in base excision DNA repair. Assuming that certain genetic traits are common for solid tumours, we have investigated wherever variations in SMUG1 and NEIL2 genes display an association with BC risk, prognosis, and therapy response in a group of 673 BC patients and 675 healthy female controls. Patients with TC genotype of NEIL2 rs6997097 and receiving only hormonal therapy displayed markedly shorter overall survival (HR = 4.15, 95% CI = 1.7-10.16, P = 0.002) and disease-free survival (HR = 2.56, 95% CI = 1.5-5.7, P = 0.02). Our results suggest that regulation of base excision repair glycosylases operated by miRNAs may modulate the prognosis of hormonally treated BC.
Keywords: DNA-lyasa (apurinová nebo apyrimidinová); dospělí; Prognosis; mikro RNA; senioři nad 80 let; studie případů a kontrol; DNA Glycosylases; nádory prsu; přežití bez známek nemoci; Disease-Free Survival; Humans; běloši; lidé středního věku; Middle Aged; Aged, 80 and over; Risk; Breast Neoplasms; riziko; prognóza; Adult; Uracil-DNA Glycosidase; DNA-glykosylasy; DNA-(Apurinic or Apyrimidinic Site) Lyase; ženské pohlaví; White People; 3' nepřekládaná oblast; jednonukleotidový polymorfismus; MicroRNAs; lidé; Case-Control Studies; Polymorphism, Single Nucleotide; DNA Repair; oprava DNA; uracil-DNA-glykosidasa; Aged; 3' Untranslated Regions; senioři; Female